Graphene-based materials for microstrip patch antenna - Nur I. Z., Azman; Muhammad K., Othman; Nur A. A., Zaini; Mohamad Ashry, Jusoh (Electromagnetics Academy, 2022)
Microstrip patch antennas are becoming increasingly relevant because of their advantages such as light weight, low costs, and ease of fabrication. To enhance the performance of an antenna, graphene was included into the fabrication of the microstrip patch antenna. Because of its numerous excellent characteristics, graphene has gained attention in recent years as a leading material. In this research, a microstrip patch antenna based on graphene was fabricated and tested at 5 GHz. The fabrication started with the production of graphene paste and was screen printed onto RT duroid 5880 substrates. To verify the binding between the graphene paste and the substrate, an adhesion test was performed on the finished graphene-based patch antenna using the Scotch tape method. The performance of fabricated antenna was measured using vector network analyzer (VNA) which includes return loss and bandwidth. The findings of the measurements were compared with the simulation results that were generated by the High Frequency Structure Simulator (HFSS). The return loss of the graphene-based antenna was measured to be -17.6314 dB, which is a little bit lower than the simulated value of -18.0597 dB that was generated by the HFSS software. The calculated bandwidth for simulated and fabricated graphene-based patch antenna were found at 156 MHz and 297.4 MHz, respectively. Based on the findings, it can be concluded that the return loss result indicates that the fabricated graphene-based patch antenna agrees well with the simulated patch antenna, although the fabricated patch antenna has a greater bandwidth than the simulated antenna.